The Influence of Women In The Board, Board Composition, and Profitability on Corporate Social Responsibility with Earnings Management as Moderating Variable: (Study on companies Registered at JII 2016-2020) - Nia Dyah Setiani Ali (Profesional Muda Cendekia Publishing, 2022)
This study aims to determine the effect of the Percentage Of Women In The Board, The Board Composition, and Profitability toward Corporate Social Responsibility with Earning Management As Moderating Variable. This research is quantitative. Data were obtained from companies registered with JII for the 2016-2020 period. The population obtained is 47 companies. The sample used in this study was 10 companies with a purposive sampling method. The analytical tools used are multiple linear regression and Moderated Regression Analysis (MRA). The data processing tool uses eviews 11. The result of this study indicates that the women in the board, profitability, and earning management have no effect on corporate social responsibility, while board composition has a significant and positive effect on corporate social responsibility. Earning management can moderate the board composition to corporate social responsibility, but cannot moderate women in the board and profitability to corporate social responsibility.